Astrocytic NDRG2 is involved in glucocorticoid-mediated diabetic mechanical allodynia. Issue 1 (April 2015) - Zuo, Zhong-Fu; Liao, Yong-Hui; Ding, Tan; Dong, Yu-Lin; Qu, Juan; Wang, Jian; Wei, Yan-Yan; Lu, Ya-Cheng; Liu, Xue-Zheng; Li, Yun-Qing
Highlights Activation of SDH astrocytes plays a vital role in diabetic mechanical allodynia. Glucocorticoids contribute to diabetic tactile allodynia partly via SDH astrocytes. NDRG2 is involved in glucocorticoid-induced activation of SDH astrocytes. This work extends glucocorticoid-induced diabetic allodynia from neuron to astrocyte.